A randomized, double‐blind, placebo‐controlled, dose‐finding trial with Lolium perenne peptide immunotherapy. Issue 4 (22nd December 2017) - Mösges, R.; Kasche, E. M.; Raskopf, E.; Singh, J.; Sohlich, L.; Astvatsatourov, A.; Shah‐Hosseini, K.; Pirotton, S.; Haazen, L.; Durham, S. R.; Legon, T.; Zadoyan, G.; et al.
Abstract: Background: A novel subcutaneous allergen immunotherapy formulation (gpASIT+™) containing Lolium perenne peptides (LPP) and having a short up‐dosing phase has been developed to treat grass pollen–induced seasonal allergic rhinoconjunctivitis. We investigated peptide immunotherapy containing the hydrolysate from perennial ryegrass allergens for the optimum dose in terms of clinical efficacy, immunogenicity and safety. Methods: This prospective, double‐blind, placebo‐controlled, phase IIb, parallel, four‐arm, dose‐finding study randomized 198 grass pollen–allergic adults to receive placebo or cumulative doses of 70, 170 or 370 μg LPP. All patients received weekly subcutaneous injections, with the active treatment groups reaching assigned doses within 2, 3 and 4 weeks, respectively. Efficacy was assessed by comparing conjunctival provocation test (CPT) reactions at baseline, after 4 weeks and after completion. Grass pollen–specific immunoglobulins were analysed before and after treatment. Results: Conjunctival provocation test (CPT) response thresholds improved from baseline to V7 by at least one concentration step in 51.2% (170 μg; P = .023), 46.3% (370 μg), and 38.6% (70 μg) of patients receiving LPP vs 25.6% of patients receiving placebo (modified per‐protocol set). Also, 39% of patients in the 170‐μg group became nonreactive to CPT vs 18% in the placebo group. Facilitated allergen‐binding assays revealed a highly significant ( P < .001) dose‐dependent reduction in IgE allergen binding across all treatment groups (70 μg: 17.1%; 170 μg: 18.8%; 370 μg: 26.4%). Specific IgG4 levels increased to 1.6‐fold (70 μg), 3.1‐fold (170 μg) and 3.9‐fold (370 μg) (mPP). Conclusion: Three‐week immunotherapy with 170 μg LPP reduced CPT reactivity significantly and increased protective specific antibodies.